2020
DOI: 10.1158/1078-0432.ccr-19-2350
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Characteristics, Treatment Patterns, and Outcomes in Patients with HER2-Positive Metastatic Breast Cancer by Hormone Receptor Status from SystHERs

Abstract: Purpose: We report treatments and outcomes in a contemporary patient population with HER2-positive metastatic breast cancer (MBC) by hormone receptor (HR) status from the Systemic Therapies for HER2-positive Metastatic Breast Cancer Study (SystHERs). Experimental Design: SystHERs (NCT01615068) was an observational, prospective registry study of U.S.-based patients with newly diagnosed HER2-positive MBC. Endpoints included treatment patterns and clinical outcomes. Results: Of 977 eligible patients (enrolled fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 19 publications
4
21
0
Order By: Relevance
“…The end-of-study results of this trial revealed that patients treated with the pertuzumab-containing regimen had an OS of 57.1 months (95% confidence interval (CI) 50-72), compared with 40.8 months (95% CI 36-48) for those treated with the placebo-containing regimen, and that the eight-year OS rates were 37% (95% CI 31-42) and 23% (19)(20)(21)(22)(23)(24)(25)(26)(27)(28), respectively [41]. Endocrine therapy was excluded in this trial, yet is frequently added after the completion of taxane therapy in routine practice, as endorsed in the guidelines [7] and supported by the registHER and SystHER observational studies, which showed clinically meaningful improvements in outcomes of patients with HR+/HER2+ BC treated with maintenance endocrine therapy [75,76].…”
Section: Metastatic Settingmentioning
confidence: 88%
“…The end-of-study results of this trial revealed that patients treated with the pertuzumab-containing regimen had an OS of 57.1 months (95% confidence interval (CI) 50-72), compared with 40.8 months (95% CI 36-48) for those treated with the placebo-containing regimen, and that the eight-year OS rates were 37% (95% CI 31-42) and 23% (19)(20)(21)(22)(23)(24)(25)(26)(27)(28), respectively [41]. Endocrine therapy was excluded in this trial, yet is frequently added after the completion of taxane therapy in routine practice, as endorsed in the guidelines [7] and supported by the registHER and SystHER observational studies, which showed clinically meaningful improvements in outcomes of patients with HR+/HER2+ BC treated with maintenance endocrine therapy [75,76].…”
Section: Metastatic Settingmentioning
confidence: 88%
“…12 With a larger sample size, our analysis shows the important prognostic role In addition, our results provide further evidence on the different behaviour of HER2-positive tumours according to hormone receptor status. [13][14][15][16][17][18] As compared to patients with hormone receptor-positive disease, those with hormone receptor-negative tumours had higher likelihood to relapse within 12 months following completion of adjuvant trastuzumab and had poorer OS irrespective of TFI. These data further highlight the need to pursue in research efforts aiming to improve the outcomes of patients with metastatic HER2-positive disease with different approaches according to hormone receptor status.…”
Section: Discussionmentioning
confidence: 99%
“…The number at risk consisted of patients still alive who did not (yet) receive the HER2-targeted therapy of interest. As we expected that HR status might influence the implementation of pertuzumab and T-DM1 in the real world, we additionally looked at the implementation rate, treatment pattern for the first three lines of systemic therapy, and outcome per HR subtype [ 8 , 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%